The Crawling Ban of the Labor Day Celebration in the Age of Indonesian Transition, 1966-1968 - FX Domini BB Hera; Ari Sapto; Daya Negri Wijaya (Dinasti Research, 2025)
The dynamics of labor movements in Indonesia 1966 were shaped by the broader political and economic transformations that followed the 1965 coup attempt. The transition to Suharto's New Order regime brought about significant changes in labor relations, characterized by the suppression of independent unions and the prioritization of economic recovery over labor rights. This study used historical methods using archival primary sources and contemporaneous narratives. This research will reveal the dynamics of labor day in Indonesia in 1966-1988 as well as Indonesian politics in a historical perspective during. This research shows that Labor Day celebrations are embedded in Indonesian society. The new ruler did not easily erase the tradition of Labor Day celebrations. The abolition of Labor Day could happen after 2 years, which means 2 times the celebration was still held despite being under pressure. The celebration of Labor Day was eventually resumed illegally, but openly in 1995 (as a protest against the then regime). Post-authoritarian 1999 and since 2013, Labor Day has been declared a public national holiday by the Indonesian government.